Determining the MRI Examination Experience: The Relationship Between Waiting Times, Information Provision, and Patient Anxiety - Ádám Román; Ida Ercsey; Helga Judit Feith (Healthcare, 2026)
Background: Performance evaluation in MRI diagnostics traditionally focuses on operational metrics (e.g., waiting times), neglecting patient experience, which fundamentally determines patients’ future healthcare compliance. The aim of our study was to identify the key factors determining patient satisfaction, particularly with regard to human interactions and the psychological impacts of the examination environment. Methods: A cross-sectional questionnaire survey was conducted at eight public diagnostic centers in Hungary (N = 742). Predictors of overall satisfaction were analyzed using multivariate linear regression (IBM SPSS 27.0), examining the effects of structural (waiting list), environmental (noise, isolation, and hygiene), and interpersonal (professional competence and information provision) variables (p < 0.05; 95%CI). Results: The model explained 48.8% of the variance in patient satisfaction. The most significant positive predictor was healthcare staff competence (β = 0.349; p < 0.001), followed by confidence in the effectiveness of the examination (β = 0.208) and hygiene (β = 0.128). The distressing effect of loneliness (isolation) was identified as a key negative factor (β = −0.131; p < 0.001). In contrast, waiting time and acoustic load (noise) were not significant confounding factors in the final model. Conclusions: Our findings highlight that, according to patients’ subjective experiences, the quality of radiological care is determined by human factors and clinical trust rather than operational speed. To improve patient satisfaction, emphasis should be placed not only on technical advancements but also on enhancing staff communication competencies and mitigating the experience of isolation during examinations.